Rhodobacteraceae dominate the core microbiome of the sea star Odontaster validus (Koehler, 1906) in two opposite geographical sectors of the Antarctic Ocean - Buschi, Emanuela; Dell’Anno, Antonio; Tangherlini, Michael; Stefanni, Sergio; Lo Martire, Marco; Núñez-Pons, Laura; Avila, Conxita; Corinaldesi, Cinzia (Frontiers in Microbiology, 2023)
Microbiota plays essential roles in the health, physiology, and in adaptation of marine multi-cellular organisms to their environment. In Antarctica, marine organisms have a wide range of unique physiological functions and adaptive strategies, useful for coping with extremely cold conditions. However, the role of microbiota associated with Antarctic organisms in such adaptive strategies is underexplored. In the present study, we investigated the diversity and putative functions of the microbiome of the sea star Odontaster validus, one of the main keystone species of the Antarctic benthic ecosystems. We compared the whole-body bacterial microbiome of sea stars from different sites of the Antarctic Peninsula and Ross Sea, two areas located in two opposite geographical sectors of the Antarctic continent. The taxonomic composition of O. validus microbiomes changed both between and within the two Antarctic sectors, suggesting that environmental and biological factors acting both at large and local scales may influence microbiome diversity. Despite this, one bacterial family (Rhodobacteraceae) was shared among all sea star individuals from the two geographical sectors, representing up to 95% of the microbial core, and suggesting a key functional role of this taxon in holobiont metabolism and well-being. In addition, the genus Roseobacter belonging to this family was also present in the surrounding sediment, implying a potential horizontal acquisition of dominant bacterial core taxa via host-selection processes from the environment.